2019
DOI: 10.1016/j.dyepig.2017.09.028
|View full text |Cite
|
Sign up to set email alerts
|

The role of auxiliaries in the immersion dyeing of textile fibres: Part 6 analysis of conventional models that describe the manner by which inorganic electrolytes promote reactive dye uptake on cellulosic fibres

Abstract: This is a repository copy of The role of auxiliaries in the immersion dyeing of textile fibres: Part 6 analysis of conventional models that describe the manner by which inorganic electrolytes promote reactive dye uptake on cellulosic fibres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 69 publications
0
27
0
Order By: Relevance
“…The amount of electrolyte used in M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 4 reactive exhaust dyeing varies, typically, between 30 and 100 gl -1 of NaCl or Na SO 4 ; as such, outrageously high levels of inorganic electrolyte are habitually used in the immersion application of reactive dyes to cellulosic fibres. Such usage poses severe environmental and economic difficulties, not simply because of because of the large amounts of electrolyte that utilised in dyeing but also, the significant environmental hazards associated with the pronounced salinity of reactive dyeing wastewater (1,6).…”
Section: Reactive Dyesmentioning
confidence: 99%
See 2 more Smart Citations
“…The amount of electrolyte used in M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 4 reactive exhaust dyeing varies, typically, between 30 and 100 gl -1 of NaCl or Na SO 4 ; as such, outrageously high levels of inorganic electrolyte are habitually used in the immersion application of reactive dyes to cellulosic fibres. Such usage poses severe environmental and economic difficulties, not simply because of because of the large amounts of electrolyte that utilised in dyeing but also, the significant environmental hazards associated with the pronounced salinity of reactive dyeing wastewater (1,6).…”
Section: Reactive Dyesmentioning
confidence: 99%
“…In the context of the mechanism of adsorption of reactive dyes on cellulosic fibres, as reactive dyes bear a close structural resemblance to direct dyes (6), it is assumed that in the absence of dye-fibre reaction (ie prior to the dye forming a covalent reaction with the cellulosic fibre), the adsorption of reactive dyes occurs in a manner analogous to that of direct dyes (9). Furthermore, the mechanism by which added inorganic electrolyte promotes reactive dye uptake prior to dye-fibre fixation is also assumed to be analogous to that described for direct dye uptake (9).…”
Section: Reactive Dyesmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown (5) that because adding inorganic electrolyte to a direct dye dyebath and reducing the liquor ratio used for dyeing achieve the same outcome, namely promotion of direct dye uptake, it is possible to dye cotton to realistic depths of shade using direct dyes in the absence of added inorganic electrolyte through the use of very low liquor ratios. In an attempt to clarify the manner by which added NaCl or Na 2 SO 4 influences reactive dye uptake on cellulosic substrates, the previous part of the paper (6) presented an analysis of published research findings relating to the promotional impact of added inorganic electrolyte on reactive dye uptake.…”
Section: Introductionmentioning
confidence: 99%
“…In this part of the paper, the findings from this analysis (6) are used to develop a theoretical model which explains the promotional effect imparted by added inorganic electrolyte on reactive dye M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 3 uptake; it will be shown that the same model can also explain the promotional impact of reduced liquor ratio on reactive dye uptake.…”
Section: Introductionmentioning
confidence: 99%